Affirmative action in antidiscrimination law and policy : an overview and synthesis - Leiter, Samuel, 1922- (SUNY series in American constitutionalism., 2002)
"Affirmative action has been and continues to be the flashpoint of America's civil rights agenda. Yet while the affirmative action literature is voluminous, no comprehensive account of its major legal and public policy dimensions exists. Samuel and William M. Leiter examine the origin and growth of affirmative action, its impact on American society, its current state, and its future anti-discrimination role, if any. Informed by several different disciplines - law, history, economics, sociology, political science, urban studies, and criminology - the text combines the relevant legal materials with analysis and commentary from a variety of experts. This even-handed presentation of the subject of affirmative action is sure to be a valuable aid to those seeking to understand the issue's many complexities."--Jacket